Problem behaviours and parenting in preschool children with cystic fibrosis. Issue 5 (20th January 2009) - Ward, C; Massie, J; Glazner, J; Sheehan, J; Canterford, L; Armstrong, D; Jaffe, A; Hiscock, H
Abstract : Background: Problems with sleep, eating and adherence to therapy may adversely affect health outcomes in children with cystic fibrosis (CF). Data on the prevalence of such problems, associated parenting styles and caregiver mental health are limited. Aims: To determine: (a) the prevalence of sleep, mealtime, therapy adherence and externalising and internalising behavioural problems in preschool children with CF; (b) the prevalence of caregiver mental health problems and poor sleep quality; and (c) associations between child behavioural problems and parenting styles. Methods: This was a cross sectional survey of caregivers of children aged 6 months to 5 years attending CF outpatient clinics at Royal Children's Hospital (Melbourne), Monash Medical Centre (Melbourne) and Sydney Children's Hospital. Main outcome measures were child externalising and internalising behaviours, sleep, eating and adherence with therapy; the predictor was parenting styles (harsh, inconsistent, overprotective). Results: 117 of 139 families participated. Problems were common with child sleep (small problem: 31.6%; moderate/large problem: 21.9%), eating (32.4%) and adherence with physiotherapy (50.4%). Compared to normative data, sleep and mealtime problems were more prevalent. Caregivers reported high rates of symptoms indicating depression (33.3%), anxiety (16.4%) and stress (34.2%). Harsh parenting was associated with internalising behaviours (adjusted OR 3.9, 95% CI 1.16 to 13.17, p = 0.03). Conclusions: Problems with sleeping, eating and physiotherapy adherence were common in preschool children with CF. Caregivers reported high rates of symptoms indicative of mental health problems. Harsh parenting was associated with internalising problems. An intervention targeting child problem behaviours and parental mental health would be appropriate for CF families.